Coronary atherosclerosis in apparently healthy master athletes discovered during pre-PARTECIPATION screening. Role of coronary CT angiography (CCTA). (1st May 2019) - Gervasi, Salvatore Francesco; Palumbo, Laura; Cammarano, Michela; Orvieto, Sebastiano; Di Rocco, Arianna; Vestri, Annarita; Marano, Riccardo; Savino, Giancarlo; Bianco, Massimiliano; Zeppilli, Paolo; Palmieri, Vincenzo
Abstract: Background: Pre-participation screening (PPS) of athletes aged over 35 years (master athletes, MA) is a major concern in Sports Cardiology. In this population, sports-related sudden cardiac death is rare but usually due to coronary atherosclerosis (CA). Coronary CT Angiography (CCTA) has changed the approach to diagnosis/management of CA, but its role in this context still needs to be assessed. Methods and results: We retrospectively examined 167 MA who underwent CCTA in our hospital since 2006, analyzing symptoms, stress-test ECG, cardiovascular risk profiles (SCORE) and CCTA findings. Among the whole enrolled population, 153 (91.6%) MA underwent CCTA for equivocal/positive stress-test ECG with/without symptoms, 13 (7.8%) just for clinical symptoms, 1 (0.6%) for the family history. The CCTA showed the presence of CA in 69 MA (41.3%), congenital coronary anomalies (anomalous origin or deep myocardial bridge) in 8 (4.8%), both in 7 (4.2%). A negative CCTA was observed in 83 MA (49.7%). The risk-SCORE (age, hypertension, hypercholesterolemia, smoking) was a good indicator for the presence of moderate/severe CA on CCTA. However, mild/moderate CA was present in 17.8% of MA clinically stratified at a low risk-SCORE. Conclusion: While coronary angiography is more indicated in athletes with positive stress-test ECG and high clinical risk, the CCTA may be useful in the evaluation of MA with an abnormal stress test ECG and/or clinical symptoms engaged in competitive sports with a high cardiovascular involvement. Age, gender, presence of symptoms and clinical risk-SCORE assessment may help sports physicians and cardiologists to decide whether to request a CCTA or not. Highlights: CCTA documented atherosclerosis (CA) in half of our master athletes (MA) with altered stress ECG. Risk-SCORE is a good indicator of CA's presence at the CCTA. However, 17.8% of MA with a low SCORE had equally mild/moderate CA. We recommend CCTA in MA (males/postmenopausal females) with impaired stress ECG, moderate/high risk-SCORE and/or symptoms.